Analisis EBIT-EPS Dalam Hubungannya Dengan Keputusan Pendanaan Perusahaan - Purba, Jan Horas V; Effendy, Marwan; Kirana, Resti (LPPM Institut Bisnis dan Informatika Kesatuan, 2014)
The purpose of this study is to examine the funding policy decision taken by the management company or whether it should use alternate equity financing or debt financing altematives using analysis of EBIT-EPS indifference point through calculations and conduct analyzes related to EBIT-EPS indifference point and corporate funding in the period 2006-2011. The analytical method used is the ratio analysis to determine the value of each variable, correlation coeficient to determine the relationship between variables, coefficient of determination to measure the relationship between variables, and the regression coeficient, where the authors used a simple linear regression with t-test and f-test to measure the effect of independent variables on the dependent variable. Keywords: EBIT-EPS indifference point, funding decisions